Implementation of a Targeted Screening Program to Detect Airflow Obstruction Suggestive of Chronic Obstructive Pulmonary Disease within a Presurgical Screening Clinic - Chantal Robitaille; Esther Dajczman; Andrew M Hirsch; David Small; Pierre Ernst; Dana Porubska; Mark Palayew (Canadian Respiratory Journal)
BACKGROUND: Targeted spirometry screening for chronic obstructive pulmonary disease (COPD) has been studied in primary care and community settings. Limitations regarding availability and quality of testing remain. A targeted spirometry screening program was implemented within a presurgical screening (PSS) clinic to detect undiagnosed airways disease and identify patients with COPD/asthma in need of treatment optimization.